VD_FINDINFO Décision / 2011 / 407 vom 12. Mai 2011 - VD Tribunal cantonal (2011)
CLASSEMENT DE LA PROCÉDURE, DIFFAMATION, SOUSTRACTION D'UNE CHOSE MOBILIÈRE | 141 CP, 173 ch. 1 CP, 310 CPP (CH), 393 al. 1 let. a CPP (CH), 393 CPP (CH)